Ebola virus epidemic disease its modeling and stability analysis required abstain strategies. Issue 1 (1st January 2018) - Tahir, Muhammad; Inayat Ali Shah, Syed; Zaman, Gul; Muhammad, Sher
Abstract: This article discusses the Ebola virus, which is also known as Ebola haemorrhagic. Ebola virus is a transmitter virus, and the transmitting agents are wild animals, whereas in the human population it transmits from human to human. We consider the Susceptible-Exposed-Infected-Recovered (SEIR) model for our study, where the population is affected by Ebola virus by wild and domestic animals. First, we formulate the proposed model. Then, the key value, R 0, is obtained, which is the reproductive number of the concerned model. After that, stability analyses, both local and endemic stabilities, are carried out for disease-free equilibria and endemic equilibria and we show that both are stable. Global stability at the disease-free as well as at endemic equilibrium was found to be successfully stable. For global stability at both levels, we define the Lapnuov function, finally, numerical simulation of the Runge–Kutta method is presented for the proposed model.